Mental and physical health burden and quality of life in Czech women with lipedema - Kunzová, Monika; Lagová, Eliška; Keith, Leslyn (Frontiers in Global Women's Health, 2025)
BackgroundLipedema is a chronic condition characterized by excessive fat deposition in the hips, buttocks, and lower legs, significantly impacting quality of life. In Czechia, limited research exists on the relationship between lipedema symptoms and depressive symptoms, despite the condition's prevalence and its impact on mental health.AimThis study aims to investigate the relationship between lipedema symptoms and the severity of depressive symptoms among Czech women and assess their quality of life.MethodsWe administered an online survey to 43 women with lipedema. Participants completed questionnaires on quality of life (WHOQOL-BREF), sociodemographic and clinical characteristics, and depressive symptoms severity, evaluated using the PHQ-9 tool.ResultsPHQ-9 results showed that 50.9% of participants exhibited moderate to severe depressive symptoms. Quality of life ratings varied, with 27.9% of participants rating their health as poor or very poor. Significant correlations were found between lipedema symptoms, such as shortness of breath, muscle stiffness, and depression severity, indicating a complex relationship between physical symptoms and mental health.ConclusionThese findings highlight the significant mental health burden faced by individuals with lipedema. The association between physical and depressive symptoms emphasizes the need for comprehensive, tailored interventions, especially integrated mental and physical healthcare approaches, aimed at improving overall well-being in this population.